0399 Effectiveness of a multidisciplinary intervention among Dutch construction workers on respirable quartz exposure: results from the 'Relieved Working Study'. (23rd June 2014) - van Deurssen, Erik; Oude Hengel, Karen; Spaan, Suzanne; Goede, Henk; Meijster, Tim; Tielemans, Erik; Heederik, Dick; Pronk, Anjoeka
Abstract : Objectives: A multidisciplinary intervention study aimed at reducing quartz exposure in the Dutch construction industry was performed. We aimed to assess the effect of the intervention on exposure level and psycho-social and organisational factors. Method: Eight participating construction companies were randomly allocated to an intervention (n = 4) or control group (n = 4). Following the Intervention Mapping approach, the intervention aimed at engineering, organisational and psycho-social factors. Pre and post-intervention respirable quartz measurements (n = 300) were taken from workers from all eight companies. Questionnaires and observation forms were used to assess pre and post psycho-social and organisational factors. Results: Pre-intervention assessment demonstrated highest respirable quartz levels for concrete drillers, tuck pointers and demolishers (GM respectively 0.20, 0.18 and 0.12 mg/m 3 ), exceeding the Dutch occupational exposure limit (OEL) in 62% of the measurements. Identified control measures resulted in 30% reduction in quartz exposure. More social influence was associated with a 1.5 fold increased use of control measures. The post intervention assessments will become available early 2014. Conclusions: High exposure levels exceeding the Dutch OEL were observed. Associations between organisational, psycho-social and use of control measures found during the pre-intervention, were taken into consideration when developing the intervention strategy. A comparison between pre and post intervention outcomes will be presented during the conference. The effect of changes in exposure levels as a result of the intervention will be assessed with a health impact assessment model incorporating population dynamics.